VALUE CO-CREATION: ENGAGING EMPLOYEE THROUGH VIRTUAL EMPLOYEE ENGAGEMENT PLATFORM (VEEP) - Cattleya Rejito (Gapenas Publisher, 2023)
The purpose of this paper is to examine the virtual employee engagement platform using a value co-creation perspective. To implement the virtual platform, the author's first entrance is using the theory acceptance model to introduce the perceived implementation of technology in the organization. Employees become the customer of the co-creation context to exchange value with the organization. The purpose blueprint has been created to support the developing platform process. Author's purpose is to combine the traditional way of physical facilities with the virtual. So the organization could manage the employees that require working in remote access without coming to the office by controlling them using the virtual platform